SIMULASI SISTEM DINAMIS MENGENAI PENGGUNAAN PUPUK SEMI ORGANIK UNTUK MENINGKATKAN PROFITABILITAS - Santi Amalia Handayani; Hery Murnawan (Journal Industrial Engineering and Management (JUST-ME), 2025)
Dynamic systems are a modeling approach to understanding the behavior of complex systems that change over time through cause-and-effect relationships between variables. In agricultural practice, fertilization is an important part of crop care, where some of the need for chemical fertilizers is met through government subsidies. However, the remaining needs must be met with high-priced non-subsidized fertilizers, resulting in increased operational costs. This condition also occurs in Gombang Village, one of the villages located in Pakel District, Tulungagung Regency, which faces similar challenges in managing agricultural costs, so the dynamic systems approach is relevant to analyzing the effectiveness of fertilizer use in increasing farmer profitability in the area. This dynamic system is carried out with the help of STELLA software, STELLA is used to design a strategy to increase profitability by compiling two scenarios. The first scenario, the use of superior seeds increases the average profitability by 31,271,686,263. The second scenario, the use of semi-organic fertilizers increases the average profitability by 38,494,816,533.